2006
DOI: 10.1158/1078-0432.ccr-05-2818
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence for the Same Clonal Origin of Multifocal Papillary Thyroid Carcinomas

Abstract: Purpose: Patients with papillary thyroid carcinoma often have two or more distinct papillary tumors at thyroidectomy. Whether these multifocal papillary lesions are clonally related or whether they arise independently is unknown as previous studies have shown conflicting results. Molecular analysis of microsatellite alterations and X-chromosome inactivation status in separate tumors from the same patient can be used to define the genetic relationships among the multiple coexisting tumors. Experimental Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 30 publications
0
53
1
2
Order By: Relevance
“…Although the study by McCarthy et al (19) reported that multifocality is highly homologous within the gland and is not associated with tumor invasion, Shindo et al (17) and Chow et al (20) found that neck lymph node metastasis and tumor multifocality remain significantly correlated, which is the major reason for lymph node metastasis. The present study is consistent with their findings.…”
Section: Discussionmentioning
confidence: 98%
“…Although the study by McCarthy et al (19) reported that multifocality is highly homologous within the gland and is not associated with tumor invasion, Shindo et al (17) and Chow et al (20) found that neck lymph node metastasis and tumor multifocality remain significantly correlated, which is the major reason for lymph node metastasis. The present study is consistent with their findings.…”
Section: Discussionmentioning
confidence: 98%
“…26,28 The clonality of the samples was evaluated on the basis of a polymorphism of the X-linked human androgen receptor gene (HUMARA) locus. 26,[28][29][30] This technique is dependent on digestion of DNA with the methylation-sensitive restriction enzyme HhaI, PCR amplification of the HUMARA locus and the detection of methylation at this locus. With this method, only the methylated HUMARA allele is amplified by PCR.…”
Section: Detection Of X-chromosome Inactivationmentioning
confidence: 99%
“…It was reported that multifocal PTC was more likely to have nodal and pulmonary metastases, as well as persistent disease (Mazzaferri et al 1977). X-chromosome inactivation in female cases and a narrow panel of loss of heterozygosity (LOH) were used to identify the clonality of multifocal PTC and 50-87% of the cases were found to arise from the same clone (Shattuck et al 2005, McCarthy et al 2006. The importance to separate multifocal independent primary (IP) PTC from PTC with intrathyroid metastasis is unclear.…”
Section: Introductionmentioning
confidence: 99%